Effect of Home Base Glucose Monitoring & Self Dose Adjustment of Insulin on Glycosylated Hemoglobin - Maulik Shah; Triya Malde; Falgun Gondalia; Sonal Shah (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: Type1 Diabetes Mellitus (T1DM) is the most common endocrine metabolic disorder of childhood casing significant mortality and morbidity in childhood. Home Monitoring of Blood Glucose (HMBG) and Supplements of insulin as required depending on the blood glucose level at that time is a very important aspect of management in T1DM. The Goal of this study was to determine whether frequent checking of home base blood glucose (HMBG) levels accompanied with insulin self dose adjustment, will lead to improved metabolic control as assessed by reduction in the Glycosylated hemoglobin values (HbA1c).Subject and Method:This study was conducted in G.G.Hospital,,M.P.Shah Medical college,Jamanagar between October 2012 to September 2013 for a period of 1 year including OPD and ward patients. Retrospective analysis of clinical profile of 37patients with T1DM attending our OPD between the age group of 2 to 16 years.A detailed clinical and family history, educational level of parents and insulin regime and insulin dose was recorded. Result:Age distribution in our study showed that 62% cases in the age of more than 10 years, 32% cases in the age group 5-10years and 2 % cases falling in the age group 0-2 years, with male to female ratio of a 1:1.7. The most frequently seen symptoms were polyuria (53%), breathlessness (48%),polydipsia (46%), vomiting (29%) of cases and 82%of the patients were ketotic at the time of presentation. In family members most common associated co-morbidity is type 2 DM(21% ) , hypertension(21%) & thyroid dysfunction (19%). split regimen was observed in (70%)and basal bolus regime in (30%). split mix regime 11(42%) had good(<7GHb) wheaeas Basal bolus regime 6(54%) of them had good control p=0.0308(<0.05). Conclusion:Regular Home monitoring of Blood glucose(HMBG) along with education on diabetes self management and regular contact with a member of a medical team for insulin dose adjustments with advice on meal planning and physical activity improve the metabolic control (as assessed by HbA1c levels) in children with T1DM.